Hands on with Google Data Studio : a data citizen's survival guide - Hurst, Lee (Computer software developer) (Wiley, 2020)
Learn how to easily transform your data into engaging, interactive visual reports! Data is no longer the sole domain of tech professionals and scientists. Whether in our personal, business, or community lives, data is rapidly increasing in both importance and sheer volume. The ability to visualize all kinds of data is now within reach for anyone with a computer and an internet connection. Google Data Studio, quickly becoming the most popular free tool in data visualization, offers users a flexible, powerful way to transform private and public data into interactive knowledge that can be easily shared and understood. Hands On With Google Data Studio teaches you how to visualize your data today and produce professional quality results quickly and easily.' No previous experience is required to get started right away'all you need is this guide, a Gmail account, and a little curiosity to access and visualize data just like large businesses and organizations. Clear, step-by-step instructions help you identify business trends, turn budget data into a report, assess how your websites or business listings are performing, analyze public data, and much more. Practical examples and expert tips are found throughout the text to help you fully understand and apply your new knowledge to a wide array of real-world scenarios. This engaging, reader-friendly guide will enable you to: -Use Google Data Studio to access various types of data, from your own personal data to public sources -Build your first data set, navigate the Data Studio interface, customize reports, and share your work -Learn the fundamentals of data visualization, personal data accessibility, and open data API's -Harness the power of publicly accessible data services including Google's recently released Data Set Search -Add banners, logos, custom graphics, and color palettes Hands On With Google Data Studio: A Data Citizens Survival Guide is a must-have resource for anyone starting their data visualization journey, from individuals, consultants, and small business owners to large business and organization managers and leaders. '